Functional alkylimidazolium ionic liquids as lubricants for steel/aluminum contact: Influence of the functional groups on tribological performance. (March 2018) - Han, Yunyan; Qiao, Dan; Sun, Liming; Feng, Dapeng
Abstract: Four different functional alkylimidazolium (1-hydroxyethyl-3-methylimidazolium, 1-carboxyethyl-3-methylimidazolium, 1-cyanopropyl-3-methylimidazolium and 1-benzyl-3-methylimidazolium) dibutyl phosphate ionic liquids were synthesized and used as lubricants for steel/Al alloy. The influence of functional groups on physicochemical properties and tribological properties was investigated and compared with 1-butyl-3-methylimidazolium dibutyl phosphate. As expected, viscosities increase when the functional groups are tethered to imidazolium cations. The tribological properties of the functional ionic liquids with three polar functional groups in cations are improved, especially the anti-wear performance and load-carrying capacity. On the contrary, the ionic liquid with benzyl group in cation shows worse tribological performance. It is considered that the functional groups in the imidazolium cations tune the adsorption of ionic liquids onto the alloy surface, which finally affect the tribological performance. Graphical abstract: Highlights: Four different functional alkylimidazolium ionic liquids were synthesized. The influences of the functional groups on the physicochemical properties were concluded. Influences of functional groups on tribological performances were also studied. Polar groups have positive effect while benzyl group has negative effect on the tribological performance of the ILs. Functional groups tune the tribological performance by adsorption.